2008
DOI: 10.2174/092986708784567680
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Development of Matrix Metalloproteinase Inhibitors

Abstract: Matrix metalloproteinases (MMPs) are a family of zinc-dependent proteinases involved in the degradation and remodeling of extracellular matrix proteins that are associated with the tumorigenic process. MMPs promote tumor invasion and metastasis, regulating host defense mechanisms and normal cell function.Thus, MMP inhibitors (MMPIs) are expected to be useful for the treatment of diseases such as cancer, osteoarthritis, and rheumatoid arthritis. A vast number of MMPIs have been developed in recent years. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 0 publications
1
61
0
5
Order By: Relevance
“…MeOH SHE, the most active sample according to current results, was suggested to be formed mostly with phenol-based compounds which are common bioactive substances of brown algae with health beneficial effects (Bhatnagar and Kim 2010) while H 2 O and n-BuOH SHE possibly contain more glycol-based compounds. Some MMP-inhibiting polysaccharides (Tu et al 2008) and benzopyran derivates from different sources were already isolated and reported while similar compounds were also found in S. horneri with different bioactivities. Nevertheless, current results indicated that S. horneri is a source for MMP inhibitors that might lead to future development of anti-tumor compounds.…”
Section: Discussionmentioning
confidence: 83%
“…MeOH SHE, the most active sample according to current results, was suggested to be formed mostly with phenol-based compounds which are common bioactive substances of brown algae with health beneficial effects (Bhatnagar and Kim 2010) while H 2 O and n-BuOH SHE possibly contain more glycol-based compounds. Some MMP-inhibiting polysaccharides (Tu et al 2008) and benzopyran derivates from different sources were already isolated and reported while similar compounds were also found in S. horneri with different bioactivities. Nevertheless, current results indicated that S. horneri is a source for MMP inhibitors that might lead to future development of anti-tumor compounds.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, Rho-GTPase is frequently overexpressed in several cancers, whereby increased activity correlates with tumor progression and underlines the different modes of tumor cell motility during invasion and metastasis. The skill of tumor cells to switch between different modes of motility has been shown to limit the efficiency of agents aimed to reduce invasion (41). Recently, besides the well-known importance of mesenchymal motility in cancer cells invasion, growing evidence show the importance of proteolysis-independent movements in neoplastic cells (27,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…MMP inhibitors have been used in a number of different therapeutic contexts to block excess MMP activity (42). In previous studies, MMP inhibitors prevented CD16 downmodulation but did not impact CD107a expression following stimulation with K562 cells (19,20).…”
Section: Mmp Expression Is Elevated In Chronic Hiv-1 Infectionmentioning
confidence: 99%